The roles of starch branching enzymes and starch synthase in the biosynthesis of amylose in rice. (March 2022) - Okpala, Nnaemeka Emmanuel; Aloryi, Kelvin Dodzi; An, Tianyue; He, Longxin; Tang, Xiangru
Abstract: Rice starch is made up of amylose; which are linear chains of α(1–4)-linked glucose residues; and amylopectin which are highly branched chains, containing α-1, 6 branch linkages. Amylose content is a very important trait used in determining rice grain quality. It is also used to determine the suitability of rice starch for industrial purposes. Rice with moderately high amylose are thought to have better grain quality, compared to those with very low or very high amylose. However, the biosynthesis of amylose in rice is a very complex biological process, which is influenced by several factors. The aim of this paper was to examine the roles of the isoforms of starch branching enzymes and the isoforms of starch synthase in the biosynthesis of amylose in rice. QTL mapping studies have shown that the primary gene responsible for amylose content is the waxy gene. In rice, the waxy gene has two major alleles, waxy a, and waxy b . Waxy a are widely distributed in indica rice varieties, while waxy b are distributed in japonica rice varieties. Granule-bound starch synthase I—an isoform of starch synthase—has the greatest impact on the amylose content of rice; while BEIIb－an isoform of starch branching enzyme－has the greatest impact on amylopectin biosynthesis in rice. This paper offers recommendations on the processes that are not fully elucidated in amylose biosynthesis and how understanding them will not only help rice breeders and producers to improve the amylose content of rice, but will also help in the development of sophisticated amylose testing methods. Graphical abstract: Image 1 Highlight: Rice starch is made up of amylose and amylopectin. Amylose content percentage can be used to determine rice grain quality. Granule-bound starch synthase I—an isoform of starch synthase—has the greatest impact on the amylose content of rice. BEIIb－an isoform of starch branching enzyme－has the greatest impact on amylopectin biosynthesis in rice.